Sosialisasi dan Edukasi tentang Risiko Hukum dan Kesehatan Reproduksi Akibat Pernikahan Dini pada Remaja di SMA Negeri 2 Kabupaten Mamuju - Andi Nasir; Syafruddin Ali Salaka; Yasirul Muntaha (STIKES Marendeng Majene, 2026)
This community service activity aimed to improve the knowledge and skills of students at SMA Negeri 2 Mamuju Regency regarding the legal and reproductive health aspects associated with the risks of early marriage. The activities were conducted through counseling, education, mentoring, and the use of FlipHTML5 as an Android-based digital learning medium. The activity stages included coordination with the partner school, development of a pocketbook and “Stop Early Marriage” posters, and evaluation of students’ knowledge and skills through pre-tests and post-tests, The results showed an improvement in students’ knowledge, with the mean score increasing from 44.28 in the pre-test to 84.20 in the post-test. Students’ skills also improved, with the mean score increasing from 65.80 to 88.76. These findings indicate that the use of FlipHTML5 as an educational medium can improve students’ knowledge and skills in understanding the risks of early marriage.